Heuristic optimization based-fixed structure robust H∞ loop shaping controller design with automatic weights selection of controllable distributed generations for Microgrid stabilization - Vachirasricirikul, Sitthidet; Ngamroo, Issarachai (My University, 2012)
In the microgrid with wind and solar power generations, the power fluctuation from such intermittent sources is an inevitable problem. To handle such situation, the distributed generations (DG) with controllable power i.e., electrolyzer (ES) and microturbine (MT) can be applied. This paper proposes a heuristic optimization based-fixed structure robust H∞ loop shaping controller design with automatic weights selection of controllable DGs for microgrid stabilization. To guarantee the system robust stability margin, the normalized coprime factorization is applied to represent unstructured uncertainties. The proportional integral (PI) is selected as the controller structure of ES and MT. For comparison purpose, the particle swarm optimization (PSO) and genetic algorithm (GA) are applied to optimize the PI parameters based on the H∞ loop shaping design. Simulation results show that the PSO-based control design is superior to GA-based controller design in terms of computation efficiency, robustness against system uncertainties and stabilizing effect. © 2012 Praise Worthy Prize S.r.l. - All right reserved.
Keywords: Distributed generations; Genetic algorithm; Heuristic optimization; Loop shaping control; Microgrid; Normalized coprime factorization; Particle swarm optimization